IMPLEMENTASI PEMBINAAN KEMANDIRIAN BAGI ANAK DIDIK PEMASYARAKATAN DI LEMBAGA PEMBINAAN KHUSUS ANAK KELAS 1 KUTOARJO - Bagus Tri Pamungkas (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This writing aims to explain the implementation of self-reliance development for andikpas at the Kutoarjo Class 1 Special Development Institute for children. This research uses Management Theory from James A.F. Stoner, to find out the right management in the implementation of self-reliance development at the Kutoarjo Class 1 Special Development Institution. The research method that the author uses is qualitative research. With primary data obtained directly from officials and staff at the Class 1 Kutoarjo Special Guidance Institute for Children, especially for binadik kasi, binadik staff and coaching officers. Data collection techniques were obtained by interview, observation and documentation. This research used descriptive-analysis research specifications. This research took place in LPKA Class 1 Kutoarjo. The results showed that in the Special Guidance Institution for Class 1 Kutoarjo children there were 5 self-reliance coaching for their correctional students, namely: sandal making activities, fishing activities, batik making activities, agate making activities and agricultural activities